Identifying preventable risk factors for hospitalised asthma in young Aboriginal children: a whole-population cohort study. Issue 6 (8th January 2021) - Brew, Bronwyn; Gibberd, Alison; Marks, Guy B; Strobel, Natalie; Allen, Clare Wendy; Jorm, Louisa; Chambers, Georgina; Eades, Sandra; McNamara, Bridgette
Abstract : Background: Australia has one of the highest rates of asthma worldwide. Indigenous children have a particularly high burden of risk determinants for asthma, yet little is known about the asthma risk profile in this population. Aim: To identify and quantify potentially preventable risk factors for hospitalised asthma in Australian Aboriginal children (1–4 years of age). Methods: Birth, hospital and emergency data for all Aboriginal children born 2003–2012 in Western Australia were linked (n=32 333). Asthma was identified from hospitalisation codes. ORs and population attributable fractions were calculated for maternal age at birth, remoteness, area-level disadvantage, prematurity, low birth weight, maternal smoking in pregnancy, mode of delivery, maternal trauma and hospitalisations for acute respiratory tract infection (ARTI) in the first year of life. Results: There were 705 (2.7%) children hospitalised at least once for asthma. Risk factors associated with asthma included: being hospitalised for an ARTI (OR 4.06, 95% CI 3.44 to 4.78), area-level disadvantage (OR 1.58, 95% CI 1.28 to 1.94), being born at <33 weeks' gestation (OR 3.30, 95% CI 2.52 to 4.32) or birth weight <1500 g (OR 2.35, 95% CI 1.39 to 3.99). The proportion of asthma attributable to an ARTI was 31%, area-level disadvantage 18%, maternal smoking 5%, and low gestational age and birth weight were 3%–7%. We did not observe a higher risk of asthma in those children who were from remote areas. Conclusion: Improving care for pregnant Aboriginal women as well as for Aboriginal infants with ARTI may help reduce the burden of asthma in the Indigenous population.